البنى الأسلوبية في ديوان ترانيم كعبي يتكئ على التوباد – للشاعر رمضان بونكانو - رضواني، نور الدين; دريدي، محمود; فطحيزة علي، ياسين (University of Eloued جامعة الوادي, 2025)
تسعى هذه الدراسة إلى الكشف عن البنى الأسلوبية المتضمنة في ديوان ترانيم كعبي يتكيء على التوباد للشاعر رمضان بونكانو وذلك من خلال اعتماد المنهج الأسلوبي فالديوان تضمن عدة ظواهر أسلوبية ساهمت في إبراز الخصائص الفنية والجمالية للديوان ففي البنى التركيبية مزج الشاعر بين الجمل الفعلية والاسمية مع سيطرة للجمل الفعلية كما نوع الشاعر في توظيف الأفعال فجاءت بأزمنة متنوعة ( الماضي - المضارع الأمر). كما استخدم الشاعر انزياحات لغوية تمثلـت فـــي التقديم والتأخير، كما نوع في توظيف الجمل الإنشائية التي عرفت حضورا بأساليب مختلفة منها الاستفهام والنداء والأمر. أما عن البني الصوتية : ففي جانب الإيقاع الخارجي فقد استخدم الشاعر البحــور الصافية في ديوانه الذي عرف سيطرة البحر البسيط ، مع ورود انزياحات واضحة على المستوى العروضي تمثلت في الزحافات والعلل وفي البنية الدلالية عرف الديوان تنوعا على مستوى الحقول الدلالية شملت ) الطبيعة والحب والدين والتاريخ ) كما وظف صورا بيانية ساهمت في تقوية المعنى وأضفت عليها طابعا جماليا، من بينها التشبيه والاستعارة. كما استعمل الشاعر التناص ممثلا في التناص الديني الذي استحضره من خلال تناصه مع القرآن الكريم في عدة قصائد ، وكذلك التناص الأدبـي مــن خــلال تناصه مع أشعار مختلفة من التراث الأدبي العربي القديم والحديث. This study seeks to reveal the stylistic structures included in the divan of the Kaabi hymn leaning on the tubad by the poet Ramadan bonkano through the adoption of the stylistic approach The office included several stylistic phenomena that contributed to highlighting the artistic and aesthetic characteristics For the Cabinet In the compositional structures, the poet mixed phrasal and nominal sentences with the control of phrasal verbs The poet was also kind in employing verbs, so they came in various tenses ( past - present order). The poet also used linguistic shifts represented in the introduction and delay, and he also used structural sentences that defined presence in various ways, including questioning, calling and ordering. As for the vocal structure : in the aspect of the external rhythm, the poet used the clear seas in his diwan, which defined the control of the simple sea , with clear displacements at the transverse level represented by skis and booms . In the semantic structure, the Diwan defined a variety at the level of semantic fields, including (nature, love, religion, history). He also employed graphic images that contributed to strengthening the meaning and gave it an aesthetic character, including analogy and metaphor. The poet also used intertextuality, represented by the religious intertextuality that he evoked through his interaction with the Holy Quran in several poems, as well as literary intertextuality through his interaction with various poems from the ancient and modern Arab literary heritage.
مذكرة .ماستر . نقد عربي حديث ومعاصر 2025
Keywords: البنـــي – الأسلوب – الأسلوبية – التناص - البني الصوتية – البنى التركيبية – البنى الدلالية . Structure-style-Stylistics-intertextuality-acoustic structures-compositional structures – Semantic structures